Cholera returns to southern Vietnam in an outbreak associated with consuming unsafe water through iced tea: A matched case-control study. - Thuong V Nguyen; Quang D Pham; Quoc K Do; Tai T Diep; Hung C Phan; Thang V Ho; Hong T Do; Lan T Phan; Huu N Tran (Public Library of Science (PLoS), 2017)
BACKGROUND:After more than a decade of steadily declining notifications, the number of reported cholera cases has recently increased in Vietnam. We conducted a matched case-control study to investigate transmission of cholera during an outbreak in Ben Tre, southern Vietnam, and to explore the associated risk factors. METHODOLOGY/PRINCIPAL FINDINGS:Sixty of 71 diarrheal patients confirmed to be infected with cholera by culture and diagnosed between May 9 and August 3, 2010 in Ben Tre were consecutively recruited as case-patients. Case-patients were matched 1:4 to controls by commune, sex, and 5-year age group. Risk factors for cholera were examined by multivariable conditional logistic regression. In addition, environmental samples from villages containing case-patients were taken to identify contamination of food and water sources. The regression indicated that drinking iced tea (adjusted odds ratio (aOR) = 8.40, 95% confidence interval (CI): 1.84-39.25), not always boiling drinking water (aOR = 2.62, 95% CI: 1.03-6.67), having the main source of water for use being close to a toilet (aOR = 4.36, 95% CI: 1.37-13.88), living with people who had acute diarrhea (aOR = 13.72, 95% CI: 2.77-67.97), and little or no education (aOR = 4.89, 95% CI: 1.18-20.19) were significantly associated with increased risk of cholera. In contrast, drinking stored rainwater (aOR = 0.17, 95% CI: 0.04-0.63), eating cooked seafood (aOR = 0.27, 95% CI: 0.10-0.73), and eating steamed vegetables (aOR = 0.22, 95% CI: 0.07-0.70) were protective against cholera. Vibrio cholerae O1 Ogawa carrying ctxA was found in two of twenty-five river water samples and one of six wastewater samples. CONCLUSIONS/SIGNIFICANCE:The magnitude of the cholera outbreak in Ben Tre was lower than in other similar settings. This investigation identified several risk factors and underscored the importance of continued responses targeting cholera prevention in southern Vietnam. The association between drinking iced tea and cholera and the spread of V. cholerae O1, altered El Tor strains warrant further research. These findings might be affected by a number of limitations due to the inability to capture asymptomatic or mildly symptomatic infections, the possible underreporting of personal unhygienic behaviors, and the purposive selection of environmental samples.